Advanced electrochemical biosensing of pathogens: Harnessing the antimicrobial properties of Ib-M peptides for highly sensitive bacterial detection - J.L. Ropero-Vega; Y.J. Galvis-Curubo; J. M. Flórez-Castillo (PLoS ONE, 2025)
This study describes the development of electrochemical biosensors with high sensitivity to detect pathogenic bacteria, including Escherichia coli O157:H7, Pseudomonas aeruginosa , and Staphylococcus aureus , in aqueous environments. The biosensors employ the antimicrobial peptides Ib-M1 and Ib-M6 as biorecognition elements, immobilized on gold nanoparticle-modified screen-printed electrodes via a self-assembled monolayer. Detection was achieved through electrochemical impedance spectroscopy, achieving remarkably low limits of detection of 1.4 CFU/mL for E. coli O157:H7 and S. aureus , and 0.8 CFU/mL for P. aeruginosa . The biosensors exhibited linear detection ranges of 0–100 CFU/mL for E. coli O157:H7 and S. aureus , and 0–75 CFU/mL for P. aeruginosa . Notably, the incorporation of carbon nanotubes significantly improved analytical sensitivity of the biosensors, particularly for E. coli O157:H7 and S. aureus . These results highlight the potential of the proposed biosensors for rapid, on-site monitoring of microbial contamination in drinking water, food processing environments, and clinical settings.